Fierce feminine divinities of Eurasia and Latin America : Baba Yaga, Kālī, Pombagira, and Santa Muerte /: Baba Yaga, Kālī, Pombagira, and Santa Muerte. ([2015]) - Oleszkiewicz-Peralba, Małgorzata, 1954-
No abstract available